Viruses and Their Interactions With Bacteria and Archaea of Hypersaline Great Salt Lake - Bhattarai, Bishav; Bhattacharjee, Ananda S.; Coutinho, Felipe H.; Goel, Ramesh K. (Frontiers in Microbiology, 2021)
Viruses play vital biogeochemical and ecological roles by (a) expressing auxiliary metabolic genes during infection, (b) enhancing the lateral transfer of host genes, and (c) inducing host mortality. Even in harsh and extreme environments, viruses are major players in carbon and nutrient recycling from organic matter. However, there is much that we do not yet understand about viruses and the processes mediated by them in the extreme environments such as hypersaline habitats. The Great Salt Lake (GSL) in Utah, United States is a hypersaline ecosystem where the biogeochemical role of viruses is poorly understood. This study elucidates the diversity of viruses and describes virus–host interactions in GSL sediments along a salinity gradient. The GSL sediment virosphere consisted of Haloviruses (32.07 ± 19.33%) and members of families Siphoviridae (39.12 ± 19.8%), Myoviridae (13.7 ± 6.6%), and Podoviridae (5.43 ± 0.64%). Our results demonstrate that salinity alongside the concentration of organic carbon and inorganic nutrients (nitrogen and phosphorus) governs the viral, bacteria, and archaeal diversity in this habitat. Computational host predictions for the GSL viruses revealed a wide host range with a dominance of viruses that infect Proteobacteria, Actinobacteria, and Firmicutes. Identification of auxiliary metabolic genes for photosynthesis (psbA), carbon fixation (rbcL, cbbL), formaldehyde assimilation (SHMT), and nitric oxide reduction (NorQ) shed light on the roles played by GSL viruses in biogeochemical cycles of global relevance.